Navigating the Regulatory Landscape: A Comprehensive Analysis - Uppal, Palak; Shukla, Vikesh; Sharma, Navneet (Journal of Social Science and Humanities, 2025)
This paper provides a comprehensive overview of the regulatory framework governing cosmetics in India. It explores the various laws, regulations, and guidelines that govern the manufacturing, import, labeling, and sale of cosmetics in the country. The paper also examines the role of regulatory authorities and their enforcement mechanisms to ensure consumer safety and product quality. The cosmetics industry in India has witnessed remarkable growth in recent years, driven by increasing consumer awareness, changing beauty trends, and rising disposable incomes. However, this flourishing industry operates within a complex regulatory framework that has evolved over time to ensure the safety, efficacy, and quality of cosmetic products. This paper provides an in-depth examination of cosmetics regulations in India, shedding light on the key regulatory bodies, the legal framework, and the challenges faced by industry stakeholders